Efficiency of Islamic Rural Banks (BPRS) in East Java Province, Indonesia - Endiarjati Dewandaru Sadono (Institute for Research and Community Empowerment (LPPM TAZKIA), 2017)
Abstract. This study aims to measure technical efficiency and identify factors that affect technical inefficiency of Islamic rural banks (BPRS) in East Java Province, Indonesia. We also want to test whether BPRS operating in districts are more efficient than those operating in cities. Data that we use are unbalanced panel data from 2011 until 2016 using stochastic frontier analysis. This study has successfully identified that the technical efficiency of BPRS operation is 90.12 percent. It means that there is still about 9.88 percent that can be optimized to improve their performance. Factors that cause technical inefficiency are Capital Adequacy Ratio (CAR) and Net Performing Financing (NPF). To improve technical efficiency of BPRS operations, the effort that must be made is to ensure each BPRS has sufficient capital stock to be channeled into loans. In addition, BPRS should also ensure the risks of bad loans are minimum.